A vertically aligned ion channel solid-state polymer electrolyte and a preparation method and application thereof

CN122889831APending Publication Date: 2026-10-09BEIHANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611091457.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

然而,现有的大多数包含二维快离子导体的聚偏氟乙烯基固态聚合物电解质的锂离子电导率仍然有限,且无法兼顾界面稳定性

Benefits of technology

[0016]本发明提供的垂直排列离子通道固态聚合物电解质在电池以及用于制备智能调光器件中的离子传导层、植入式光纤传感器中的敏感元件、忆阻器中的离子迁移介质或柔性离子电子器件中的信号传导层中也具有很好的应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889831A_ABST
    Figure CN122889831A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of solid electrolyte, in particular to a kind of vertical arrangement ion channel solid polymer electrolyte and its preparation method and application.The present application provides a kind of vertical arrangement ion channel solid polymer electrolyte, composition includes polymer matrix, 1-butyl-3-methyl imidazole cation intercalation montmorillonite nanosheet and lithium salt, the 1-butyl-3-methyl imidazole cation intercalation montmorillonite nanosheet is vertically arranged in polymer matrix.The vertical arrangement ion channel solid polymer electrolyte provided by the present application has vertical arrangement, interlayer confined lithium ion transport channel, can guide lithium ion transmission path from polymer matrix to the interlayer channel of two-dimensional filler, both can effectively improve ion conductivity, and also can weaken solvent interaction to improve the interface compatibility of solid polymer electrolyte, to significantly improve the cycle stability of solid lithium metal battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid electrolyte technology, specifically to a solid polymer electrolyte with vertically arranged ion channels, its preparation method, and its application. Background Technology

[0002] Incorporating inorganic conductive fillers into polyvinylidene fluoride (PVDF) solid polymer electrolytes is considered a promising method to improve effective lithium-ion conductivity. Among various fillers, two-dimensional fast ion conductors have attracted widespread attention due to their higher specific surface area and better dispersibility compared to bulk materials, which facilitates the formation of continuous lithium-ion transport pathways. However, most existing PVDF solid polymer electrolytes containing two-dimensional fast ion conductors still exhibit limited lithium-ion conductivity and fail to maintain interfacial stability. Summary of the Invention

[0003] Therefore, the purpose of this invention is to provide a solid polymer electrolyte with vertically aligned ion channels, its preparation method, and its applications. The solid polymer electrolyte with vertically aligned ion channels provided by this invention exhibits high lithium-ion conductivity and excellent interfacial stability.

[0004] To achieve the above-mentioned objectives, the present invention provides the following technical solution: The present invention provides a solid polymer electrolyte with vertically arranged ion channels, comprising a polymer matrix, 1-butyl-3-methylimidazolium cation-intercalated montmorillonite nanosheets and a lithium salt, wherein the 1-butyl-3-methylimidazolium cation-intercalated montmorillonite nanosheets are vertically arranged in the polymer matrix.

[0005] Preferably, the polymer matrix comprises one or more of polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride polymer, and polyethylene oxide; The mass ratio of the 1-butyl-3-methylimidazolium cationic intercalated montmorillonite nanosheets to the polymer matrix is ​​1:1~2.

[0006] Preferably, the lithium salt comprises one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate, and lithium tetrafluoroborate; The mass ratio of the 1-butyl-3-methylimidazolium cationic intercalated montmorillonite nanosheets to the lithium salt is 1:1~3.

[0007] This invention also provides a method for preparing the vertically aligned ion channel solid polymer electrolyte described in the above technical solution, comprising the following steps: The polymer, lithium salt, and first organic solvent are mixed to obtain a polymer-lithium salt solution; 1-Butyl-3-methylimidazolium cationic intercalated montmorillonite, lithium salt, and a second organic solvent were mixed to obtain an intercalated montmorillonite-lithium salt dispersion. The polymer-lithium salt solution and the intercalated montmorillonite-lithium salt dispersion were mixed and then formed into a film to obtain the precursor film; The solid polymer electrolyte precursor membrane is cut to obtain precursor membrane sheets. Several precursor membrane sheets are stacked to obtain a stack. The stack is hot-pressed to obtain the vertically arranged ion channel solid polymer electrolyte.

[0008] Preferably, the thickness of the precursor film is 50~300μm; The number of precursor membrane layers in the stack is 10 to 600. The hot pressing temperature is 120~160℃, and the time is 5~120min.

[0009] Preferably, the concentration of the polymer in the polymer-lithium salt solution is 10~300 g / L; The first organic solvent includes one or more of N-methylpyrrolidone, acetonitrile, dimethylformamide, and dimethylacetamide.

[0010] Preferably, the concentration of 1-butyl-3-methylimidazolium cationic intercalated montmorillonite in the intercalated montmorillonite-lithium salt dispersion is 10~300 g / L; The second organic solvent includes one or more of N-methylpyrrolidone, acetonitrile, dimethylformamide, and dimethylacetamide.

[0011] Preferably, the preparation method of the 1-butyl-3-methylimidazolium cationic intercalated montmorillonite includes the following steps: mixing lithium-based montmorillonite and a 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt solution and carrying out an ion exchange reaction to obtain 1-butyl-3-methylimidazolium cationic intercalated montmorillonite.

[0012] The present invention also provides the application of the vertically aligned ion channel solid polymer electrolyte described in the above technical solution or the vertically aligned ion channel solid polymer electrolyte prepared by the preparation method described in the above technical solution in batteries.

[0013] The present invention also provides the application of the vertically aligned ion channel solid polymer electrolyte described in the above technical solution or the vertically aligned ion channel solid polymer electrolyte prepared by the preparation method described in the above technical solution in smart dimming devices, implantable fiber optic sensors, memristors or flexible ion electronic devices.

[0014] This invention provides a vertically aligned ion channel solid polymer electrolyte comprising a polymer matrix, 1-butyl-3-methylimidazolium cation-intercalated montmorillonite nanosheets, and a lithium salt, wherein the 1-butyl-3-methylimidazolium cation-intercalated montmorillonite nanosheets are vertically aligned within the polymer matrix. The vertically aligned ion channel solid polymer electrolyte provided by this invention possesses vertically aligned, interlayer-confined lithium-ion transport channels. This invention uses 1-butyl-3-methylimidazolium cation-intercalated montmorillonite nanosheets (denoted as BMMT) as a two-dimensional filler, which not only promotes lithium salt dissociation but also self-assembles within the polymer matrix to form interlayer-confined nanochannels. The nanoconfining effect in the BMMT nanochannels induces a layered distribution of cations and anions, guiding the lithium-ion transport path from the polymer matrix to the interlayer channels of the BMMT. This effectively improves the ionic conductivity of the solid polymer electrolyte and significantly reduces solvent interactions, enhancing the interfacial compatibility of the solid polymer electrolyte and thus significantly improving the cycle stability of solid-state lithium metal batteries.

[0015] In the vertically aligned ion channel solid polymer electrolyte provided by this invention, the vertically oriented BMMT significantly shortens the lithium-ion transport path. The altered lithium-ion solvation structure within the confined space of the BMMT transforms lithium-ion transport behavior from solvent-assisted migration to interlayer diffusion, significantly reducing residual solvent in the solid polymer electrolyte, thereby suppressing interfacial side reactions and improving flame retardancy.

[0016] The vertically aligned ion channel solid polymer electrolyte provided by this invention also has good application prospects in batteries, as well as in ion conduction layers for preparing smart dimming devices, sensitive elements in implanted fiber optic sensors, ion migration media in memristors, or signal conduction layers in flexible ion electronic devices.

[0017] As shown in the test results of the examples, the solid polymer electrolyte with vertically aligned ion channels containing vertically oriented BMMT provided by the present invention exhibits a significantly improved lithium-ion conductivity, increasing from 0.16 mS / cm to 1.17 mS / cm, while the lithium-ion transference number increases from 0.21 to 0.62. The reactive solvent molecule content is effectively reduced to below 2.8 wt%, and remains below 0.2 mA / cm. 2 and 0.2mAh / cm 2 Stable cycling for 1400 hours under stable conditions.

[0018] This invention employs an integrated slicing-stacking method to successfully prepare a vertically aligned ion channel solid electrolyte with vertically arranged, interlayer-confined lithium-ion transport channels. The preparation method provided by this invention is simple to operate, has low production costs, is environmentally friendly, and is suitable for industrial production. Attached Figure Description

[0019] Figure 1 The diagram shows the BMMT preparation process and the characterization diagrams of Li-MMT and BMMT. In the diagram, A is the BMMT preparation process, B is the scanning electron microscope (SEM) image of Li-MMT, C is the Zeta potential test results of Li-MMT and BMMT, D is the SEM image of BMMT, E is the transmission electron microscope (TEM) image of BMMT, F is the X-ray diffraction (XRD) pattern of Li-MMT and BMMT, and G is the infrared spectrum of Li-MMT and BMMT. Figure 2 A schematic diagram of the integrated slice-stack method; Figure 3 This is a graph showing the reactive solvent molecule content of the vertically aligned ion channel solid polymer electrolyte (VBMP film) prepared in Example 1. Figure 4 The graph shows the lithium-ion conductivity test results of the VBMP thin film prepared in Example 1. Figure 5 The LSV voltage-current curve of the VBMP thin film prepared in Example 1; Figure 6 The graph shows the lithium-ion conductivity test results of the VBMP thin film prepared in Example 2; Figure 7 The graph shows the lithium-ion conductivity test results of the VBMP thin film prepared in Example 3; Figure 8 The graph shows the lithium-ion conductivity test results of the VBMP thin film prepared in Example 4; Figure 9 The diagram shows the reactive solvent molecule content of the pH membrane prepared in Comparative Example 1. Figure 10 The reactive solvent molecule content diagram is shown for the MPH membrane prepared in Comparative Example 2. Figure 11 The graph shows the reactive solvent molecule content of the BMPH membrane prepared in Comparative Example 3. Figure 12 The graph shows the lithium-ion transference number test results of the pH film (a) prepared for Comparative Example 1, the MPH film (b) prepared for Comparative Example 2, the BMPH film (c) prepared for Comparative Example 3, and the VBMP film (d) prepared for Example 1. Figure 13 The activation energy test results of the pH membrane prepared for Comparative Example 1, the MPH membrane prepared for Comparative Example 2, the BMPH membrane prepared for Comparative Example 3, and the VBMP thin film prepared for Example 1 are shown in the figure. Figure 14 The graph shows the symmetrical battery cycle performance test results of the pH membrane prepared in Comparative Example 1, the MPH membrane prepared in Comparative Example 2, the BMPH membrane prepared in Comparative Example 3, and the VBMP thin film prepared in Example 1. Detailed Implementation

[0020] The present invention provides a solid polymer electrolyte with vertically arranged ion channels, comprising a polymer matrix, 1-butyl-3-methylimidazolium cation-intercalated montmorillonite nanosheets and a lithium salt, wherein the 1-butyl-3-methylimidazolium cation-intercalated montmorillonite nanosheets are vertically arranged in the polymer matrix.

[0021] In this invention, the 1-butyl-3-methylimidazolium cationic intercalated montmorillonite nanosheets (denoted as BMMT, structural schematic shown in [reference needed]) Figure 1 The thickness can be 1~10nm, or 2~5nm, specifically 1nm, 2nm, 3nm, 4nm or 5nm.

[0022] In this invention, the polymer matrix may include one or more of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP, structural formula shown in Formula 1), polyvinylidene fluoride polymer, and polyethylene oxide. Formula 1.

[0023] In this invention, the mass ratio of the 1-butyl-3-methylimidazolium cationic intercalated montmorillonite nanosheets to the polymer matrix can be 1:1~2, or 1:1.2~1.8, or even 1:1.4~1.6, or specifically 1:1.5.

[0024] In this invention, the lithium salt may include one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium hexafluorophosphate (LiPF6), and lithium tetrafluoroborate (LiBF4). In this invention, the mass ratio of the 1-butyl-3-methylimidazolium cationic intercalated montmorillonite nanosheets to the lithium salt may be 1:1 to 3, or 1:1.5 to 2.5, specifically 1:2.

[0025] The vertically aligned ion channel solid polymer electrolyte provided by this invention benefits from the altered lithium-ion solvation structure within the confined space of 1-butyl-3-methylimidazolium cation-intercalated montmorillonite nanosheets, thereby enhancing the interfacial compatibility of the solid polymer electrolyte. This effectively reduces the content of reactive solvent molecules in the solid polymer electrolyte to below 2.8 wt%, and maintains a conductivity of 0.2 mA / cm². 2 and 0.2mAh / cm 2 Stable cycling for 1400 hours under stable conditions.

[0026] The vertically aligned ion channel solid polymer electrolyte provided by this invention benefits from the vertically aligned lithium-ion transport channels constructed by 1-butyl-3-methylimidazolium cation-intercalated montmorillonite nanosheets. The interlayer nanoconfining effect of the 1-butyl-3-methylimidazolium cation-intercalated montmorillonite nanosheets significantly enhances the lithium-ion transport kinetics, while the vertical alignment structure further shortens the ion diffusion path. The ionic conductivity of the vertically aligned ion channel solid polymer electrolyte can be increased to 1.17 mS / cm, and the lithium-ion transference number can reach 0.62.

[0027] This invention also provides a method for preparing the vertically aligned ion channel solid polymer electrolyte described in the above technical solution, comprising the following steps: The polymer, lithium salt, and first organic solvent are mixed to obtain a polymer-lithium salt solution (denoted as pH solution). 1-Butyl-3-methylimidazolium cationic intercalated montmorillonite, lithium salt, and a second organic solvent were mixed to obtain an intercalated montmorillonite-lithium salt dispersion (denoted as BMIMTFSI-intercalated montmorillonite dispersion). The polymer-lithium salt solution and the intercalated montmorillonite-lithium salt dispersion were mixed and then formed into a film to obtain a precursor film (denoted as BMPH film). The solid polymer electrolyte precursor membrane is cut to obtain precursor membrane sheets. Several precursor membrane sheets are stacked to obtain a stack. The stack is hot-pressed to obtain the vertically aligned ion channel solid polymer electrolyte (denoted as VBMP).

[0028] Unless otherwise specified, the materials and equipment used in this invention are all commercially available products in the field.

[0029] This invention involves mixing a polymer, a lithium salt, and a first organic solvent to obtain a polymer-lithium salt solution. In this invention, the mass ratio of the polymer to the lithium salt can be 1-2:1-3, or even 1:1-3, specifically 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 2:1, 2:1.5, 2:2.5, or 2:3. In this invention, the first organic solvent can include one or more of N-methylpyrrolidone (NMP), acetonitrile, dimethylformamide, and dimethylacetamide. In this invention, the concentration of the polymer in the polymer-lithium salt solution can be 10-300 g / L, or even 50-250 g / L, or further 100-200 g / L, specifically 150 g / L.

[0030] This invention involves mixing 1-butyl-3-methylimidazolium cationic intercalated montmorillonite, lithium salt, and a second organic solvent to obtain an intercalated montmorillonite-lithium salt dispersion.

[0031] In this invention, the second organic solvent may include one or more of N-methylpyrrolidone, acetonitrile, dimethylformamide, and dimethylacetamide.

[0032] In this invention, the concentration of 1-butyl-3-methylimidazolium cationic intercalated montmorillonite in the intercalated montmorillonite-lithium salt dispersion can be 10~300 g / L, or 50~250 g / L, or even 100~200 g / L, or specifically 150 g / L.

[0033] In this invention, the preparation method of the 1-butyl-3-methylimidazolium cationic intercalated montmorillonite (see...) Figure 1 The process may include the following steps: mixing lithium-based montmorillonite (Li-MMT), 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt and solvent solution, and carrying out an ion exchange reaction (referred to as the first ion exchange reaction) to obtain 1-butyl-3-methylimidazolium cation-intercalated montmorillonite (referred to as BMIM-MMT or BMMT).

[0034] In this invention, the mass ratio of lithium-based montmorillonite to the 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt solution can be 1:1~30, or 1:5~25, or even 1:10~20. In this invention, the concentration of the 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt solution can be 5~200 g / L, or 10~150 g / L, or even 50~100 g / L; the solvent in the 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt solution can be water.

[0035] In this invention, the temperature of the first ion exchange reaction can be 5~60℃, or 10~50℃, or even 20~40℃; the time of the first ion exchange reaction can be 2~100h, or 10~80h, or even 20~50h, specifically 24h, 30h, or 40h; during the first ion exchange reaction, Li in Li-MMT... + With 1-butyl-3-methylimidazolium cation (BMIM) + An exchange occurs.

[0036] After completing the first ion exchange reaction, the present invention may further include: centrifuging the system after the first ion exchange reaction, washing the obtained solid with water, and then freeze-drying it to obtain 1-butyl-3-methylimidazolium cationic intercalated montmorillonite (powder). In the present invention, the number of centrifugations can be 2 to 10 times, or 3 to 8 times, or even 3 to 5 times, specifically 3 times; the purpose of centrifugation is to remove impurities. The present invention does not have any particular limitation on the freeze-drying; lyophilization is sufficient.

[0037] In this invention, the preparation method of lithium-based montmorillonite may include the following steps: mixing sodium-based montmorillonite (Na-MMT), LiCl, and water, and carrying out an ion exchange reaction (referred to as the second ion exchange reaction) to obtain lithium-based montmorillonite. In this invention, the mass ratio of sodium-based montmorillonite to LiCl may be 1:0.5~8, or 1:0.5~5, or further 1:0.5~2, specifically 1:0.5 or 1:0.8. In this invention, the mixing may include: dissolving LiCl in water to obtain a LiCl aqueous solution; and dispersing sodium-based montmorillonite in the LiCl aqueous solution. In this invention, the concentration of the LiCl aqueous solution may be 1~8 g / L, or 2~7 g / L, or further 3~6 g / L, specifically 4 g / L or 5 g / L. In this invention, the temperature of the second ion exchange reaction can be 40-80℃, or 40-70℃, specifically 40℃, 50℃, or 60℃; the time of the second ion exchange reaction can be 24-72 hours, or 36-72 hours, or further 48-72 hours, specifically 60 hours, 66 hours, or 72 hours. After completing the second ion exchange reaction, this invention may further include: centrifuging the system after the second ion exchange reaction, washing the obtained solid with water to obtain lithium-based montmorillonite. In this invention, the water washing can be deionized water washing until Cl is completely removed. - This invention can test Cl using AgNO3. - Whether it is completely removed.

[0038] After obtaining a polymer-lithium salt solution and an intercalated montmorillonite-lithium salt dispersion, the present invention mixes the polymer-lithium salt solution and the intercalated montmorillonite-lithium salt dispersion and then forms a film to obtain a precursor film. In the present invention, film formation may include drying after molding. In the present invention, the molding method may include casting, blade coating, or casting. In the present invention, the drying temperature may be 50~140℃, or 60~120℃, or further 80~100℃; the drying time may be 12~48h. In the present invention, the thickness of the precursor film may be 50~300μm, or 100~250μm, or further 150~200μm. In the present invention, film formation may be performed on a glass plate.

[0039] After obtaining the precursor membrane, the present invention cuts the solid polymer electrolyte precursor membrane to obtain precursor membrane sheets, stacks several precursor membrane sheets to obtain a stack, and hot-presses the stack to obtain the vertically aligned ion channel solid polymer electrolyte (see process flow diagram). Figure 2 ).

[0040] The present invention does not have a special limitation on the size of the precursor membrane, which can be determined according to actual needs, such as 1cm~1cm×100cm~100cm.

[0041] In this invention, the number of precursor films in the stack can be 10 to 600 layers, or 30 to 500 layers, or even 50 to 400 layers, or specifically 60, 80, 100, 150, 200, 250, 300, or 350 layers.

[0042] In this invention, the hot-pressing temperature can be 120~160℃, or 130~160℃, specifically 140℃, 150℃, or 160℃; the hot-pressing time can be 5~120 min, or 8~100 min, or further 10~50 min, specifically 10 min, 15 min, 20 min, 30 min, or 40 min; the hot-pressing pressure can be 0.1~20 MPa, or 1~15 MPa, further 5~10 MPa. In this invention, the purpose of the hot-pressing is to enhance the interlayer bonding force of the precursor film.

[0043] After hot pressing, the present invention may further include: slicing the hot-pressed block laminate material to obtain a vertically aligned ion channel solid polymer electrolyte. In the present invention, the thickness of the vertically aligned ion channel solid polymer electrolyte can be 5~500μm, or 100~500μm, specifically 100μm, 200μm, 300μm, 400μm, or 500μm.

[0044] This invention employs an integrated slicing-stacking method to prepare a vertically aligned, interlayer-confined solid polymer electrolyte with vertically aligned ion channels for lithium-ion transport. Specifically, BMMT is selected as a two-dimensional filler, which not only promotes lithium salt dissociation but also self-assembles within the polymer matrix to form interlayer-confined nanochannels. The nanoconfining effect in the BMMT nanochannels induces a layered distribution of cations and anions, effectively improving the ionic conductivity of the solid polymer electrolyte. The vertically aligned BMMT prepared by the slicing and stacking method significantly shortens the lithium-ion transport path. The altered lithium-ion solvation structure within the BMMT confinement space transforms lithium-ion transport behavior from solvent-assisted migration to interlayer diffusion, significantly reducing residual solvent in the resulting solid polymer electrolyte to below 2.8 wt%, thereby suppressing interfacial side reactions and improving flame retardancy.

[0045] This invention also provides the application of the vertically aligned ion channel solid polymer electrolyte described in the above-described technical solutions, or the vertically aligned ion channel solid polymer electrolyte prepared by the preparation method described in the above-described technical solutions, in batteries. In this invention, the battery includes a solid-state lithium metal battery.

[0046] This invention also provides the application of the vertically aligned ion channel solid polymer electrolyte described in the above-described technical solutions, or the vertically aligned ion channel solid polymer electrolyte prepared by the preparation method described in the above-described technical solutions, in smart dimming devices, implantable fiber optic sensors, memristors, or flexible ion electronic devices. In this invention, the application may include using the vertically aligned ion channel solid polymer electrolyte to prepare ion conduction layers in smart dimming devices, sensitive elements in implantable fiber optic sensors, ion migration media in memristors, or signal conduction layers in flexible ion electronic devices.

[0047] The vertically aligned ion channel solid polymer electrolyte provided by this invention has vertically aligned, interlayer confined lithium-ion transport channels, which can guide the lithium-ion transport path from the polymer matrix to the interlayer channels of the two-dimensional filler. This can effectively improve the ionic conductivity and reduce solvent interaction to improve the interfacial compatibility of the solid polymer electrolyte, thereby significantly improving the cycle stability of solid lithium metal batteries. Moreover, it also has good application prospects in the fabrication of ion conduction layers in smart dimming devices, sensitive elements in implanted fiber optic sensors, ion migration media in memristors, or signal conduction layers in flexible ion electronic devices.

[0048] To further illustrate the present invention, the technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0049] Example 1 according to Figure 1 and Figure 2 Prepare a solid polymer electrolyte with vertically aligned ion channels.

[0050] (1) Disperse Na-MMT in LiCl aqueous solution (4 g / L), stir at 60 °C for 72 h, centrifuge, and wash the resulting solid with deionized water until Cl is reached. - Complete removal yielded Li-MMT with a thickness of 1.5 nm. An aqueous solution of Li-MMT and BMIMTFSI (concentration 10 g / L) was stirred at 25 °C for 24 h, centrifuged three times, and the resulting solid product was freeze-dried to obtain BMIM powder. The mass ratio of Na-MMT to LiCl was 2:1, and the mass ratio of Li-MMT to BMIMTFSI was 1:3.

[0051] (2) Disperse PVDF-HFP and LiTFSI in NMP at a mass ratio of 1:1 to obtain a pH solution (PVDF-HFP concentration is 100 g / L).

[0052] BMMT powder and LiTFSI were dispersed in NMP at a mass ratio of 1:1 to obtain BMMT-intercalated montmorillonite dispersion (BMMT concentration was 20 g / L).

[0053] The PH solution and BMIMTFSI-intercalated montmorillonite dispersion were mixed, and the resulting BMPH dispersion was coated onto a glass plate with a doctor blade and dried at 80°C for 24 h to obtain a BMPH film (100 μm thick). The mass ratio of PVDF-HFP to BMMT powder was 1:1.

[0054] The BMPH membrane was cut into BMPH membrane sheets of the same size. Sixty layers of BMPH membrane were stacked sequentially in a hot press mold and hot-pressed at 140°C for 10 minutes. The resulting block-shaped laminated material was then precisely cut into thin sheets of 200 μm thickness to obtain a solid polymer electrolyte with vertically arranged ion channels (denoted as VBMP film).

[0055] Figure 1 The diagram shows the BMMT preparation process and the characterization images of Li-MMT and BMMT. In the diagram, A represents the BMMT preparation process, B is the SEM image of Li-MMT, C is the Zeta potential of Li-MMT and BMMT, D is the SEM image of BMMT, E is the TEM image of BMMT, F is the X-ray diffraction pattern of Li-MMT and BMMT, and G is the infrared spectrum of Li-MMT and BMMT. It can be seen that the present invention successfully prepared BMMT powder.

[0056] The vertically aligned ion channel solid polymer electrolyte prepared in Example 1 has an ionic conductivity of 1.1 mS / cm, and its LSV curve shows that it can withstand a high voltage of 4.99 V, indicating that it can be matched with a high voltage positive electrode.

[0057] Figure 3 The thermogravimetric (TG) test results of the VBMP film prepared in Example 1 show that the content of reactive solvent molecules was effectively reduced to below 2.8 wt%.

[0058] Figure 4 The graph shows the lithium-ion conductivity test results of the VBMP film prepared in Example 1. It can be seen that the ion conductivity of the VBMP film is 1.1 mS / cm, which is high.

[0059] Figure 5 The LSV voltage-current curve of the VBMP film prepared in Example 1 shows that the VBMP film can withstand a high voltage of 4.99V.

[0060] Example 2 The only difference from Example 1 is that in step (2), the drying temperature is 100°C, the hot pressing temperature is 160°C, and the hot pressing time is 20 min.

[0061] Figure 6 The graph shows the lithium-ion conductivity test results of the VBMP film prepared in Example 2. It can be seen that the ionic conductivity of the VBMP film is 0.8 mS / cm, which is high.

[0062] Example 3 The only difference from Example 1 is that in step (2), the hot pressing time is 20 min and the thickness of the VBMP film is 500 μm.

[0063] Figure 7 The graph shows the lithium-ion conductivity test results of the VBMP film prepared in Example 3. It can be seen that the ionic conductivity of the VBMP film is 1 mS / cm, which is high.

[0064] Example 4 The only difference from Example 1 is that the ion exchange temperature in the preparation of Li-MMT in step (1) is 40°C; and in step (2), the drying temperature is 100°C and the thickness of the VBMP film is 100 μm.

[0065] Figure 8 The graph shows the lithium-ion conductivity test results of the VBMP film prepared in Example 4. It can be seen that the ionic conductivity of the VBMP film is 0.9 mS / cm, which is high.

[0066] Comparative Example 1 PVDF-HFP and LiTFSI were dispersed in NMP to obtain a pH solution (PVDF-HFP concentration of 100 g / L). The pH solution was then coated onto a glass plate using a doctor blade and dried at 80 °C for 24 h to obtain a pH film (thickness of 100 μm).

[0067] Figure 9 The thermogravimetric (TG) test results of the pH membrane prepared in Comparative Example 1 show that the content of reactive solvent molecules is 11 wt%.

[0068] Comparative Example 2 Montmorillonite (MMT) was dispersed in NMP to obtain an MMT dispersion (MMT concentration of 20 g / L).

[0069] PVDF-HFP and LiTFSI were dispersed in NMP at a mass ratio of 1:1 to obtain a pH solution (PVDF-HFP concentration of 100 g / L).

[0070] The MMT dispersion and pH solution were mixed, and the pH solution was coated onto a glass plate using a doctor blade. The mixture was then dried at 80°C for 24 hours to obtain an MPH film (100 μm thick). The mass ratio of MMT to PVDF-HFP was 1:1.

[0071] Figure 10 The thermogravimetric (TG) test results of the MPH membrane prepared in Comparative Example 2 show that the reactive solvent molecule content is 9.5 wt%.

[0072] Comparative Example 3 BMMT powder and LiTFSI were dispersed in NMP to obtain a BMMT-TFSI intercalated montmorillonite dispersion (BMMT concentration was 10 g / L). The BMMT-TFSI intercalated montmorillonite dispersion was coated onto a glass plate using a doctor blade and dried at 80 °C for 24 h to obtain a BMPH film (thickness was 100 μm). The mass ratio of BMMT powder to LiTFSI was 1:1.

[0073] Figure 11 The thermogravimetric (TG) test results of the BMPH membrane prepared in Comparative Example 3 show that the content of reactive solvent molecules was effectively reduced to below 6.2 wt%.

[0074] Test Example 1 The lithium-ion transference number, activation energy, and symmetric battery cycle performance of the pH membrane prepared in Comparative Example 1, the MPH membrane prepared in Comparative Example 2, the BMPH membrane prepared in Comparative Example 3, and the VBMP thin film prepared in Example 1.

[0075] 1. Lithium-ion transference number (LTL) t Li+ Determination of ) The test was conducted using a combination of potentiostatic polarization and AC impedance methods. The specific steps are as follows: The test membranes (pH membrane, MPH membrane, BMPH membrane, or VBMP thin film) were assembled into a Li / test membrane / Li symmetric blocking coin cell (CR2032). Tests were performed at room temperature (25±1℃) using an electrochemical workstation (Chenhua CHI760E).

[0076] The initial AC impedance spectrum of the battery was measured in the frequency range of 1 MHz to 0.1 Hz, with an applied AC amplitude of 10 mV, to obtain the initial interface impedance. R 0 .

[0077] Then, a DC constant potential polarization of 10mV (ΔV=10mV) was applied to the battery, and the change of polarization current over time was recorded until the current reached a steady state. The steady-state current was then recorded. I s .

[0078] After polarization, the AC impedance spectrum of the battery was measured again to obtain the interfacial impedance after polarization. R s .

[0079] The lithium-ion transport number is calculated according to Equation 1: (Equation 1); in, I 0 The initial current (i.e., the current at the instant of DC polarization before polarization) can be obtained from... ΔV / R 0 (Approximately obtained) I s For steady-state current, R 0 and R s These are the measured values ​​of the interfacial impedance before and after polarization. At least three parallel cells were tested for each sample, and the results were averaged.

[0080] 2. Activation energy ( E a Determination of ) The activation energy is calculated using the Arrhenius equation by testing the ionic conductivity at different temperatures.

[0081] The membrane under test (pH membrane, MPH membrane, BMPH membrane, or VBMP film) is sandwiched between two stainless steel blocking electrodes to assemble a stainless steel / membrane under test / stainless steel symmetric cell. Temperature-dependent AC impedance spectroscopy is performed using an electrochemical workstation (such as a Solartron 1260+1287 or similar equipment).

[0082] The test temperature range is 30~70℃, with a test point set at 10℃ intervals. At each temperature, the battery is placed in a constant temperature chamber for 30 minutes to reach thermal equilibrium.

[0083] At each temperature point T, the AC impedance spectrum was measured, with a frequency range of 1MHz to 0.1Hz and an AC amplitude of 10mV. The bulk resistance was then read from the impedance spectrum. R (The intersection of the high-frequency region and the real axis).

[0084] Calculate the ionic conductivity at this temperature using Equation 2. σ : (Equation 2); in, L The thickness of the membrane is in cm. A The effective area of ​​the membrane (cm²) 2 ).

[0085] According to the Arrhenius formula (see Equation 3): (Equation 3); After taking the logarithm, with lnσ right 1000 / T Plot a graph and perform a linear fit, using the slope of the line. -E a / (1000R) Calculation of activation energy E a (Unit: kJ·mol) -1 ),in R The ideal gas constant is 8.314 J·mol⁻¹. -1 ·K -1 Each sample was tested three times, and the average value was taken.

[0086] 3. Symmetrical battery cycle performance test The test membrane (pH membrane, MPH membrane, BMPH membrane, or VBMP thin film) was assembled into a Li / test membrane / Li symmetric coin cell. The cell assembly was completed in an argon-filled glove box (water and oxygen content were both below 0.1 ppm).

[0087] Constant current charge-discharge cycle tests were performed using a battery testing system (such as LAND CT2001A or NEWARE BTS series). The test conditions were as follows: temperature 25℃, current density 0.1 mA·cm². -2 The cycle time is 1 hour for charging and discharging (i.e., 1 hour per half cycle).

[0088] Record the change of polarization voltage (i.e., the voltage difference between charge and discharge platforms) with time / number of cycles during the cyclic process.

[0089] Figure 12 The graph shows the lithium-ion transference number test results for the pH membrane (a) prepared in Comparative Example 1, the MPH membrane (b) prepared in Comparative Example 2, the BMPH membrane (c) prepared in Comparative Example 3, and the VBMP thin film (d) prepared in Example 1. It can be seen that the lithium-ion transference numbers of the solid polymer electrolytes prepared in Comparative Examples 1-3 and Example 1 are 0.21, 0.11, 0.53, and 0.62, respectively. The VBMP thin film prepared in Example 1 has the highest lithium-ion transference number of 0.62, indicating high lithium-ion conductivity.

[0090] Figure 13 The activation energy test results of the pH membrane prepared in Comparative Example 1, the MPH membrane prepared in Comparative Example 2, the BMPH membrane prepared in Comparative Example 3, and the VBMP film prepared in Example 1 are shown in the figure. It can be seen that the activation energies of the solid polymer electrolytes prepared in Comparative Examples 1-3 and Example 1 are 0.24 eV, 0.27 eV, 0.21 eV and 0.195 eV, respectively. The VBMP film prepared in Example 1 has the lowest activation energy, indicating that its lithium ion migration barrier is the lowest.

[0091] Figure 14 The graph shows the symmetrical battery cycle performance of the pH membrane prepared in Comparative Example 1, the MPH membrane prepared in Comparative Example 2, the BMPH membrane prepared in Comparative Example 3, and the VBMP film prepared in Example 1. It can be seen that the VBMP film prepared in Example 1 has the most stable cycle stability.

[0092] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A solid polymer electrolyte with vertically aligned ion channels, comprising a polymer matrix, 1-butyl-3-methylimidazolium cation-intercalated montmorillonite nanosheets, and a lithium salt, wherein the 1-butyl-3-methylimidazolium cation-intercalated montmorillonite nanosheets are vertically aligned in the polymer matrix.

2. The solid polymer electrolyte with vertically arranged ion channels according to claim 1, characterized in that, The polymer matrix includes one or more of polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride polymer, and polyethylene oxide. The mass ratio of the 1-butyl-3-methylimidazolium cationic intercalated montmorillonite nanosheets to the polymer matrix is ​​1:1~2.

3. The solid polymer electrolyte with vertically arranged ion channels according to claim 1, characterized in that, The lithium salt includes one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate, and lithium tetrafluoroborate; The mass ratio of the 1-butyl-3-methylimidazolium cationic intercalated montmorillonite nanosheets to the lithium salt is 1:1~3.

4. A method for preparing the vertically aligned ion channel solid polymer electrolyte according to any one of claims 1 to 3, comprising the following steps: The polymer, lithium salt, and first organic solvent are mixed to obtain a polymer-lithium salt solution; 1-Butyl-3-methylimidazolium cationic intercalated montmorillonite, lithium salt, and a second organic solvent were mixed to obtain an intercalated montmorillonite-lithium salt dispersion. The polymer-lithium salt solution and the intercalated montmorillonite-lithium salt dispersion were mixed and then formed into a film to obtain the precursor film; The solid polymer electrolyte precursor membrane is cut to obtain precursor membrane sheets. Several precursor membrane sheets are stacked to obtain a stack. The stack is hot-pressed to obtain the vertically arranged ion channel solid polymer electrolyte.

5. The preparation method according to claim 4, characterized in that, The thickness of the precursor film is 50~300μm; The number of precursor membrane layers in the stack is 10 to 600. The hot pressing temperature is 120~160℃, and the time is 5~120min.

6. The preparation method according to claim 4, characterized in that, The concentration of the polymer in the polymer-lithium salt solution is 10~300g / L; The first organic solvent includes one or more of N-methylpyrrolidone, acetonitrile, dimethylformamide, and dimethylacetamide.

7. The preparation method according to claim 4, characterized in that, The concentration of 1-butyl-3-methylimidazolium cationic intercalated montmorillonite in the intercalated montmorillonite-lithium salt dispersion is 10~300g / L; The second organic solvent includes one or more of N-methylpyrrolidone, acetonitrile, dimethylformamide, and dimethylacetamide.

8. The preparation method according to claim 4, characterized in that, The preparation method of the 1-butyl-3-methylimidazolium cationic intercalated montmorillonite includes the following steps: mixing lithium-based montmorillonite and a 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt solution, and carrying out an ion exchange reaction to obtain 1-butyl-3-methylimidazolium cationic intercalated montmorillonite.

9. The application of the vertically aligned ion channel solid polymer electrolyte according to any one of claims 1 to 3 or the vertically aligned ion channel solid polymer electrolyte prepared by the preparation method according to any one of claims 4 to 8 in a battery.

10. The application of the vertically aligned ion channel solid polymer electrolyte according to any one of claims 1 to 3 or the vertically aligned ion channel solid polymer electrolyte prepared by the preparation method according to any one of claims 4 to 8 in smart dimming devices, implantable fiber optic sensors, memristors or flexible ion electronic devices.